(untitled) (Fiep Bulletin - online, 2017)
This article presents a theoretical and epistemological perspective about welcoming as an ethical andpolitical guideline of the National Humanization Policy from the Health Unique System (SUS). Its writing derived from an invitationto carry out a workshop about the theme with workers from the SUS healthcare network with emphasis on Primary Healthcareand Family Health Support Centers in a municipality from the south of Brazil this year. It consisted of a careful visit to thetheoretical frame of reference produced by a Master degree research titled Social Impact of the More Medical Doctors for BrazilProgram: a case study. This research corresponded to one unfolding of a state research underway titled Social Impact of theMore Medical Doctors in Santa Catarina, developed by the University of Vale do Itajaí, financed by the Scientific andTechnological Research Support Foundation of Santa Catarina and with direct support of the State Health Secretariat, SantaCatarina, Brazil. After reading this theoretical frame of reference, the next step was to revisit the authors related to the style ofsocial thought about health. From the interlocution among these contents, it has been conceived a theoretical andepistemological perspective configured in three dimensions: ethical and political dimension, strategic dimension and proceduraldimension. The path has revealed that the dialogue among such dimensions can favor the responsible management ofconfrontation situations in spaces of primary care actions and family health support centers for welcoming purposes.